Penerapan Telemedicine dalam Mendukung Integrasi Pelayanan Kesehatan Primer - Prima, Prima; Oktaviana L, Putri; Nurhidayati, Evi (Yayasan Inspirasi El Burhani, 2026)
Introduction: Primary health care serves as the frontline in achieving a healthy, independent, and equitable society. The implementation of the Integrated Primary Health Care (ILP) system is a strategic effort to improve efficiency, coordination, and service continuity. One of the innovations supporting ILP implementation is telemedicine, which utilizes digital technology to facilitate remote medical consultations, patient monitoring, and electronic referrals. Objective: The purpose of this service was This study aims to describe the implementation of telemedicine services in supporting ILP at Ngambon Community Health Center (Puskesmas Ngambon), Bojonegoro Regency. Method: This public service was conducted by used is a descriptive approach, with data collected through observation, interviews, and document review related to telemedicine implementation at the health center. Result: Telemedicine has improved coordination among health workers, accelerated patient referral processes, and expanded service access, especially for communities in remote areas. However, several challenges remain, including limited technological infrastructure, uneven internet connectivity, and low digital literacy among some community members. Conclusion: The implementation of telemedicine at Puskesmas Ngambon plays a significant role in strengthening ILP, yet it requires cross-sectoral support and capacity building to achieve optimal outcomes. Therefore, strong policy support, capacity building for human resources, and reinforcement of health information systems are essential to ensure the sustainability of telemedicine implementation. By optimizing telemedicine, primary healthcare services can become more responsive, efficient, and equitable in achieving the highest possible standard of public health.